Environmental factors influence on flowering and fruiting period of selected essential oil plants from Annonaceae - Dewi Ayu Lestari; Abban Putri Fiqa (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Lestari DA, Fiqa AP. 2020. Environmental factors influence on flowering and fruiting period of selected essential oil plants from Annonaceae. Biodiversitas 21: 910-921. Many species of Annonaceae family in tropics produce fragrances, due to the active ingredients for essential oils. Since the abundant of flower and fruit production, basic knowledge of flowering and fruiting periods needs to be known. The aim of this study was to determine influence of environmental factors to selected essential oil plants flowering and fruiting period from Annonaceae family, i.e. Artabotrys suaveolens, Cananga odorata, Desmos chinensis, Dasymaschalon borneense, Fissistigma latifolium, and Xylopia malayana. Observations were made throughout the year during dry and rainy season, with each phase carried out scoring qualitatively based on its abundance in plant canopy. Data on environmental factors (temperature, humidity, and rainfall intensity) were obtained from Registration Unit, Purwodadi Botanic Garden (PBG). Data of flowering and fruiting period were analyzed descriptively using Microsoft Excel, while the influence of environmental factors to flowering and fruiting period was analyzed by Biplot with Past 3.0. statistic program. Flowering period occurred in wet months at the end of year (November-December), while fruiting period occurred in long dry month. Initiation and bloom of flowering were influenced by temperature, while fruiting period was largely influenced by humidity and rainfall intensity, except for C. odorata whose fruiting period was influenced by temperature. Key words: Annonaceae, environmental factors, essential oils, flowering, fruiting